ENHANCEMENT OF MULTIPATH ROUTING PROTOCOL FOR ROUTE RECOVERY IN MANET - Pooja; Ajay Dureja (European Scientific Journal, ESJ, 2013)
Route failure is a vigorous issue in MANET that is mainly responsible for interrupted service between source and destination, so there should be some mechanism to handle this issue as soon as it is detected, to continue the transmission. In this paper we have proposed “Enhancement of Multipath Routing Protocol for Route Recovery (EMPRR) in MANET”, a routing protocol which provides multipath discovery, efficient utilization of bandwidth and controlled traffic load route recovery at the time of failure. Aproach: At the time of failure the recovery node is selected from the neighboring nodes of node detecting failure ,by performing route discovery from node detecting failure and the neighboring node which is first to send the route reply packet from the destination to the node detecting failure is selected as recovery node and if the two neighbors of failure node send the route reply packet at the same time then the node with higher available bandwidth is selected in the mean while we send stop transmission till route recovery packet to source node through reverse path, as soon as new path is selected start transmission packet is sent to source to start transmission again and updates its cache by storing new route for transmission. Results: The proposed protocol is efficient in overcoming the problem of stale routes in multipath routing protocols. Also proposed protocol shows significant improvement in packet delivery ratio and reduced end to end delay.